The First-Trimester Gestational Weight Gain Associated With de novo Hypertensive Disorders During Pregnancy: Mediated by Mean Arterial Pressure - Yuan, Zhichao; Wang, Hai-Jun; Su, Tao; Yang, Jie; Chen, Junjun; Peng, Yuanzhou; Zhou, Shuang; Bao, Heling; Luo, Shusheng; Wang, Hui; Liu, Jue; Han, Na; et al. (Frontiers in Nutrition, 2022)
The relationship between first-trimester GWG and risk of hypertensive disorders of pregnancy (HDP) remained uncertain. This study aimed to investigate the association between first-trimester GWG and risk of de novo HDP. Meanwhile, we explored the mediated effect and constructed an early GWG category to evaluate the predictive capacity for HDP. First-trimester GWG was defined as the weight difference between 13±1 gestational weeks and pre-conception. HDP group was defined as having diagnosis of de novo HDP, including gestational hypertension or de novo preeclampsia during the current pregnancy. Early GWG category was constructed according to the risk of HDP within each pre-pregnancy BMI group. Cox regression model was utilized to check the association between the first-trimester GWG and HDP. Serial mediation model was adopted to evaluate the potential mediators including mean arterial pressure at 13th and 20th week. The logistic regression model with bootstrap was performed to assess the predictive capacity of Early GWG category and mean arterial pressure for the risk of HDP. A total of 17,901 pregnant women (mean age, 29.0 years) were recruited from 2013 to 2017 at the Tongzhou Maternal and Child Health Hospital in Beijing, China. Compared to women in Class 1 of early GWG category, women in the Class 2, 3, 4 have increased risks of HDP by 1.42, 4.27 and 4.62 times, respectively (HR=2.42, 95% CI: 2.11-2.77; HR=5.27, 95% CI: 4.05-6.86; HR=5.62, 95% CI: 4.05-7.79). The mean arterial pressure measured at 13th and 20th week totally mediated 33.1% and 26.7% of association between first-trimester GWG and HDP in total participants and overweight / obesity pregnancies, respectively. The Area Under Receiver Operator Characteristic Curve for predictive model utilizing early GWG category and mean arterial pressure measured at 13th and 20th week for the risk of HDP is 0.760 (95% CI: 0.739-0.777). The first-trimester GWG was associated with de novo HDP, which was partially mediated by mean arterial pressure measured at 13th and 20th week. Early GWG category showed a better predictive capacity for the risk of HDP compared to the National Academy of Medicine criteria for first-trimester GWG.